2018
DOI: 10.12669/pjms.342.12213
|View full text |Cite
|
Sign up to set email alerts
|

Lack of uniformity in screening, diagnosis and management of gestational diabetes mellitus among health practitioners across major cities of Pakistan

Abstract: Objective:To determine knowledge, attitude and practice (KAP) regarding management of Gestational Diabetes Mellitus (GDM) among Health Care Providers in major cities of Pakistan.Methods:A knowledge, attitude and practice (KAP) questionnaire based study was conducted in major cities in Pakistan from health care providers in public and private hospitals and clinics. Questionnaires were provided to the health care providers regarding screening, diagnosis and management of patients with GDM. Data analysis was done… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Therefore, we should educate the population about the healthy lifestyle and make them aware of the grave consequences of the obesity. Moreover, Riaz RH et al, (2018) suggested that the physicians’ awareness regarding GDM up to date diagnostic and management strategies could play a pivotal role in managing GDM burden 28…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we should educate the population about the healthy lifestyle and make them aware of the grave consequences of the obesity. Moreover, Riaz RH et al, (2018) suggested that the physicians’ awareness regarding GDM up to date diagnostic and management strategies could play a pivotal role in managing GDM burden 28…”
Section: Discussionmentioning
confidence: 99%
“…The total number of doctors in the country is only 175,223 (one doctor for 1,073 individuals) and 15,106 dentists (one dentist for 12,447) (Mashhadi et al, 2016). The health sector is one of the major service sectors of the country and there are issues such as counterproductive or deviant behavior among nurses which require our scholarly attention (Riaz et al, 2018). The literature shows that such negative behaviors usually result from the supervisors' leadership style (Asrar-ul-Haq and Kuchinke, 2016).…”
Section: Introductionmentioning
confidence: 99%